Gallbladder adenosquamous carcinoma: a case report and literature review. Issue 9 (27th September 2021) - Davis, Tyler; Moudy, Paige; Abdelgawad, Mohamed; Barghuthi, Lutfi; Ismael, Hishaam
Abstract: Representing 90–95% of all malignant gallbladder neoplasms, adenocarcinoma is by far the most common subtype. Adenosquamous carcinoma is a rare subtype, accounting for only 1–5% of all gallbladder carcinomas. These tumors have been shown to have aggressive biologic behavior, commonly extending to adjacent structures. Some studies have shown that the squamous component often displayed a greater proliferative capacity than the adenocarcinomatous component (possibly even up to twice as fast). Complete surgical resection is currently the mainstay of treatment but the prognosis is often poor. In this paper, we present a case of a 69-year-old male with an AJCC Stage IV moderately differentiated adenosquamous carcinoma of the gallbladder treated with radical cholecystectomy including liver segments IVb, V, VI.